LEARNERS’ NEEDS FOR DIGITAL SELF-ASSESSMENT IN PANCASILA STUDENT PROFILE PROJECTS (P5) IN ELEMENTARY SCHOOL - Liska Auliyani Daswati; Seni Apriliya; Lutfi Nur (Jurnal Cakrawala Pendas, 2025)
The development of digital technology encourages innovation in learning assessment, including self-assessment which is important for shaping students' learning independence from an early age. However, in elementary schools, the application of digital-based self-assessment is still not optimal, especially in the context of the Pancasila Learner Profile Strengthening Project (P5) which emphasizes the value of reflection and active participation. This study aims to describe learners' needs for digital-based self-assessment, identify challenges faced, and design the concept of its development in the context of P5 in elementary schools. The research used a descriptive qualitative approach and was conducted at SDN Cimuncang with participants as many as 6 teachers and 10 learners involved in the implementation of P5. A purposive sampling technique was used to select the participants. Data were obtained through semi-structured interviews, observation of digital assessment practices in the classroom, and document analysis in the form of reflective journals and school assessment policies. Data analysis refers to the Miles and Huberman model, with the stages of data reduction, data presentation, and conclusion drawing. Triangulation of methods and member-checking were conducted to increase validity. The results showed that the self-assessment implemented did not fully support in-depth reflection, was less interesting, and did not optimally utilize technology. Learners expect more interactive and appreciative assessments. Teachers understand the importance of self-assessment, but its implementation is still limited. The development of digital self-assessment that is adaptive and aligned with P5 principles is needed to improve reflection, motivation, and learning independence.